Pengaruh Keterampilan Mengajar Menggunakan Aplikasi Bandicam terhadap Kriteria Ketuntasan Minimal (KKM) Siswa Mata Pelajaran PAI di SMA Islam Samarinda - Nur R, Dayu Rahmad (Faculty of Education and Teacher Training of UINSI Samarinda, 2022)
The Effect of Teaching Skills Using the Bandicam Application on Students' Minimum Completeness Criteria (KKM) in PAI Subjects at Samarinda Islamic High School